Proceedings of the 1st Annual Conference on Education and Social Sciences (ACCESS 2019) 2020
DOI: 10.2991/assehr.k.200827.072
|View full text |Cite
|
Sign up to set email alerts
|

From Less to More Sophisticated Solutions: A Sociomathematical Norms to Develop Students’ Self-Efficacy

Abstract: This paper is a part of a larger study which aimed to design a learning trajectory in pre-algebra. As a design research, it follows three steps of Preliminary Studies, Teaching Implementation and Retrospective Analysis. To enhance the quality of learning, we adjusted the socio-mathematical norms in the teacher's lesson plan. One aspect that will be discussed in the present study is the order of the students' solution during group and class discussion. The subjects of the study were 32 fifth grade students of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Hal ini menarik karena berdasarkan penelitian pendahulu, pembelajaran klasikal yang berlangsung secara tatap muka, interaksi multi-arah diketahui memberikan dampak besar bagi aktivitas dan hasil belajar (Goodboy & Myers, 2008;Shan et al, 2014). Biasanya bentuk interaksi ini akan menjadi optimal jika didukung dengan penerapan normal sosial dan norma sosial matematika yang terarah, misalnya dengan mengurutkan hasil diskusi dari jawaban yang paling sederhana ke jawaban yang paling kompleks (Apsari et al, 2020;Güven & Dede, 2017;Kang & Kim, 2016).…”
Section: Pembahasanunclassified
“…Hal ini menarik karena berdasarkan penelitian pendahulu, pembelajaran klasikal yang berlangsung secara tatap muka, interaksi multi-arah diketahui memberikan dampak besar bagi aktivitas dan hasil belajar (Goodboy & Myers, 2008;Shan et al, 2014). Biasanya bentuk interaksi ini akan menjadi optimal jika didukung dengan penerapan normal sosial dan norma sosial matematika yang terarah, misalnya dengan mengurutkan hasil diskusi dari jawaban yang paling sederhana ke jawaban yang paling kompleks (Apsari et al, 2020;Güven & Dede, 2017;Kang & Kim, 2016).…”
Section: Pembahasanunclassified
“…A sociomathematical norm is the consideration of a mathematically acceptable explanation in conjunction with an understanding of what has been mathematically different [13], [20], [21]. Sociomathematical norm is a thought from a group's mathematical discussion together with mathematical understanding [14], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier literature on social and sociomathematical norms focused on, among others, their development (McClain & Cobb, 2001), establishing patterns of interactions (Roy et al, 2014) and how the norms are identified (Güven & Dede, 2017) in mathematics classrooms. Recent studies link sociomathematical norms with mathematical learning and teaching experiences like self-efficacy (Apsari et al, 2020), early numeracy learning (Morrison et al, 2021), abilities in problem-solving (Dini & Maarif, 2022), mathematical process skills (Gülburnu & Gürbüz, 2022), mathematical modelling activities (Yenmez & Erbaş, 2023), and teacher noticing (Baki & Kilicoglu, 2023). This article follows these trends and explores how transforming existing sociomathematical norms enhances learners' proficiency in mathematics.…”
Section: Contribution To the Literaturementioning
confidence: 99%